Cultural Communication of Sedekah Bumi (Earth Alms) Rituals of Poggang Village Community Serangpanjang Subang during Covid-19 Pandemic - Dwinarko Dwinarko; Annisa Eka Syafrina; Tabrani Sjafrizal (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the cultural communication of sedekah bumi (earth alms) ritual in Ponggang Village community in preserving cultural values and ancestral heritage during pandemic. The theory used is Schutz's theory of communicative action that the idea of contextualization with communicative action can be developed by describing three elements of theory, namely an Action in the form of Social action, oriented to the participants present, from mediated action, which expands action into a secondary manipulator. Then, Transcendence about widely ignored categorical differences and Objectivation which deals textual differences. The method used is a descriptive qualitative narrative from direct observations, interviews, and involvement in cultural rituals by mingling with the community before and after the ritual procession. The results of the research show the Earth Alms Ritual is a communicative action through traditional meetings, preparation with mutual assistance costs, facilities and infrastructure with the active participation of traditional leaders and indigenous peoples through the division of tasks as a form of social interaction. Communicative actions are reflected through cultural meanings in various symbols or communication symbols integrated into the meaning of agricultural products, exchange of taste, intention, slaughtering goats, suro porridge, and ritual processions meaning religious values building a fertile natural environment. The pandemic atmosphere reflects the community's life to carry out ritual communicative actions to become a cultural horizon in maintaining the health and welfare of the community. Recommendations, integration of knowledge on preserving ritual culture as part of individual and community introspection actions in preventing Covid-19.